Impacts of hydrogen on tropospheric ozone and methane and their modulation by atmospheric NOx - Bryant, Hannah N.; Stevenson, David S.; Heal, Mathew R.; Abraham, Nathan Luke (Frontiers in Energy Research, 2024)
Atmospheric hydrogen concentrations have been increasing in recent decades. Hydrogen is radiatively inert, but it is chemically reactive and exerts an indirect radiative forcing through chemistry that perturbs the concentrations of key species within the troposphere, including ozone. Using the atmospheric version of the United Kingdom Earth System Model we deconstruct and analyse the impact of 10 % increased surface concentrations of hydrogen on ozone production, loss and concentrations. We also analyse the impact of this hydrogen in atmospheres with lower anthropogenic emissions of nitrogen oxides (80% and 30% of present-day anthropogenic surface emissions) as this likely better represents the outcome of the transition from fossil fuels towards renewable hydrogen. In each case, we also assess the changes in hydroxyl radical concentration and hence methane lifetime and calculate the net impact on the hydrogen tropospheric global warming potential (GWP). We find that the hydrogen tropospheric GWP will change relatively little alongside decreases in surface anthropogenic NOx emissions (9.48.9 and 9.18.6 for our present-day and 30% anthropogenic emissions, respectively). This conclusion may be impacted by future changes in emissions of other reactive species.